2012
DOI: 10.21061/jcte.v28i1.571
|View full text |Cite
|
Sign up to set email alerts
|

Predicting High School Students’ Interest in Majoring in a STEM Field: Insight into High School Students’ Postsecondary Plans

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
69
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 35 publications
11
69
0
2
Order By: Relevance
“…showing am increasing trend in scientific research, an area of inquiry, termed as Educational Data Mining (EDM) [1]. EDM aims towards discovering useful information from large amounts of electronic data collected by educational systems.…”
Section: Machine Learning Has In the Recent Years Found Larger And Wimentioning
confidence: 99%
See 1 more Smart Citation
“…showing am increasing trend in scientific research, an area of inquiry, termed as Educational Data Mining (EDM) [1]. EDM aims towards discovering useful information from large amounts of electronic data collected by educational systems.…”
Section: Machine Learning Has In the Recent Years Found Larger And Wimentioning
confidence: 99%
“…Preparing an educated workforce to enter Science, Technology, Engineering and Mathematics (STEM) careers is important for scientific innovations and technological advancements, as well as economic development and competitiveness [1]. In addition to expanding the nation's workforce capacity in STEM, broadening participation and success in STEM is also imperative for women given their historical underrepresentation and the occupational opportunities associated with these fields.…”
Section: Introductionmentioning
confidence: 99%
“…Situational interest predicts depth of cognitive processing of information (Linnenbrink-Garcia et al 2013), degree of positive affect (Ely et al 2013), and effort regulation . Personal interest predicts continued mathematics and mathematicsintensive course taking (Lichtenberger and George-Jackson 2013), mathematics achievement in the long term (Murayama et al 2013), and perhaps most importantly, mathematics identity (Mangu et al 2015)-that aspect of ourselves that integrates our self-concept and cultural role with our conception of mathematics and what makes one mathematically adept (Boaler and Greeno 2000).…”
Section: Key Individual Motivational Factorsmentioning
confidence: 99%
“…This is because, preparing an educated workforce to enter Science, Technology, Engineering and Mathematics (STEM) occupations is important for scientific innovations and technological advancements, as well as economic development and competitiveness [7]. In addition, the growth in the number of University students enrolling in STEM fields of study does not keep pace with the STEM labour market demand and on the other hand, there is indication that high school graduates' interest in and readiness for STEM fields of study have been in the decline [8], [9]. Given the growing need to attract more high school graduates into these specific postsecondary areas of study, research devoted to understanding the influences on students' academic choices in regard to postsecondary STEM majors is becoming essential [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lichtenberger and George-Jackson [9] study identified several factors that impact high school students' interest in STEM fields which may be categorized into three main themes: students' interests and motivations, academic qualification, and educational contexts. These three themes largely correspond with two of the factors included in Perna and Thomas' model; namely internal and school-level contexts [10].…”
Section: Introductionmentioning
confidence: 99%